2010
DOI: 10.1097/hcr.0b013e3181d6f962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Rehabilitation Program on Skeletal Muscle Function in Idiopathic Pulmonary Arterial Hypertension

Abstract: Peripheral muscle characteristic improvements may contribute to the clinical benefit observed following a rehabilitation program in IPAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 15 publications
6
101
0
7
Order By: Relevance
“…These improvements were in line with the increase in quadriceps muscle endurance [72]. Others found a reduction in fast-twitch muscle fibres and a potential increase in capillary density in the quadriceps of PAH patients after ExT [73].…”
Section: Improving Endurance Capacity Exercise Trainingsupporting
confidence: 59%
“…These improvements were in line with the increase in quadriceps muscle endurance [72]. Others found a reduction in fast-twitch muscle fibres and a potential increase in capillary density in the quadriceps of PAH patients after ExT [73].…”
Section: Improving Endurance Capacity Exercise Trainingsupporting
confidence: 59%
“…a 100-s or 33% improvement was reached in 30 (91%) out of 33 and 27 (82%) out of 33 investigations, respectively) (figure 1). tLIM is also responsive to rehabilitation in idiopathic PAH [121,122] and IPF [123,124]. In one observational study of 53 IPF patients, the effect size for tLIM after rehabilitation was larger than for V′O 2 peak, WRpeak, 6MWD and ISWT [123] (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Isotime V′O 2 , V′CO 2 and V′E, as well as cardiac output and [La − ] a and other variables are responsive to a number of interventions in COPD [25,62,98,99,120,[128][129][130][131] and in some other conditions such as cystic fibrosis [132] and PAH [122,133]. Isotime comparisons are also responsive outcomes of interventions directed to train arm muscles [134][135][136].…”
Section: Evaluativementioning
confidence: 98%
“…1 Previously, expert recommendations included avoidance of any exertion or activity, including pulmonary rehabilitation (PR), but there are now sufficient studies demonstrating the benefits of PR in this population. [2][3][4][5][6][7][8] These studies have demonstrated the presence of myopathic changes in skeletal musculature that are responsive to training. 3,9 They have also demonstrated meaningful outcomes in physical activity as measured by the sixminute walk test (6MWT) 4,6 as well as improvement in QOL scores postpulmonary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] These studies have demonstrated the presence of myopathic changes in skeletal musculature that are responsive to training. 3,9 They have also demonstrated meaningful outcomes in physical activity as measured by the sixminute walk test (6MWT) 4,6 as well as improvement in QOL scores postpulmonary rehabilitation. 2,5,10 The 6MWT is a part of the evaluation of patients with chronic respiratory disease in general and has been used as a part of the evaluation of pharmacotherapy in PH.…”
Section: Introductionmentioning
confidence: 99%